Diversidade e sazonalidade de abelhas Euglossini Latreille (Hymenoptera: apidae) em fitofisionomias do bioma cerrado em Uberlândia, MG - Freitas, Rafael Fosca de (2009)
The Euglossini tribe occurs in the Neotropical region, and is formed by bees typical of humid tropical forests. Studies in Brazilian Cerrado are scarce, especially when this is a mosaic of vegetation. This study aimed to verify and compare the abundance and the richness of the Euglossini bees species found in the strict sense cerrado and in the gallery forest of the Estação Ecológica do Panga (EEP) and in the strict sense cerrado of the Reserva Vegetal do Clube Caça Caça e Pesca Itororó (CCPIU), near the city of Uberlândia, MG. During the period from December 2006 to March 2008, 619 males of Euglossini, belonging to nine species, distributed in three genera of the tribe were surveyed. The most abundant species were Eulaema nigrita (54% of total), Euglossa melanotricha (26.5 %) e Euglossa imperialis (14%). The gallery forest of the EEP was the site with the highest diversity of bees. The comparison between sites showed that despite the gallery forest is more related to the cerrado of EEP, the latter shows a greater resemblance to the cerrado of CCPIU. Most species were collected in the warm and humid season, which was also the season with greater abundance. The fauna of Euglossini sampled until this date in Triângulo Mineiro, was compared with other researches from different regions of Brazil, showing a similar composition to areas of Atlantic rainforest of São Paulo and Minas Gerais. Many studies on the composition of the Euglossini fauna in the Triângulo Mineiro still need to be developed in order to understand the patterns of biogeography of these species by the Central Brazil.